Age at introduction of solid foods and feeding difficulties in childhood: findings from the Southampton Women's Survey. Issue 4 (30th June 2016) - Hollis, J. L.; Crozier, S. R.; Inskip, H. M.; Cooper, C.; Godfrey, K. M.; Robinson, S. M.
Abstract: This study aimed to determine whether age at introduction of solid foods was associated with feeding difficulties at 3 years of age. The present study was carried out using data from the Southampton Women's Survey (SWS). Women enrolled in the SWS who subsequently became pregnant were followed-up during pregnancy and postpartum, and the offspring have been studied through childhood. Maternal socio-demographic and anthropometric data and child anthropometric and feeding data were collected through interviews and self-administered questionnaires. When the children were 3 years of age, mothers/carers rated six potential child feeding difficulty questions on a four-point Likert scale, including one general question and five specific feeding difficulty questions. Age at introduction of solids as a predictor of feeding difficulties was examined in 2389 mother–child pairs, adjusting for child (age last breast fed, sex, gestation) and maternal characteristics (parity, pre-pregnancy BMI, age, education, employment, parenting difficulties, diet quality). The majority of mothers/carers (61 %) reported some feeding difficulties (general feeding difficulty question) at 3 years of age, specifically with their child eating enough food (61 %), eating the right food (66 %) and being choosy with food (74 %). Children who were introduced to solids ≥6 months had a lower risk of feeding difficulties (RR 0·73; 95 % CI 0·59, 0·91, P =0·004) than children who were introduced to solids between 4 and 6 months. No other significant associations were found. There were few associations between feeding difficulties in relation to age at introduction of solid foods. However, general feeding difficulties were less common among infants introduced to solid foods ≥6 months of age.